Assessment of the control measures of category A diseases of the Animal Health Law: Infection with rinderpest virus (Rinderpest). (25th January 2022) - ,; Nielsen, Søren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, José Luis; Gortázar, Christian; Herskin, Mette; Michel, Virginie; et al.
Abstract: EFSA received a mandate from the European Commission to assess the effectiveness of control measures against diseases included in the Category A list according to Regulation (EU) 2016/429 on transmissible animal diseases ('Animal Health Law'). This opinion belongs to a series of opinions where these control measures are assessed, with this opinion covering the assessment of control measures for rinderpest (RP), the only animal disease to have been globally eradicated. In this opinion, the AHAW Panel reviewed the effectiveness of: (i) clinical and laboratory sampling procedures, (ii) monitoring period and (iii) the minimum radius of the protection and surveillance zone, and the minimum length of time the measures should be applied in these zones. The general methodology used for this series of opinions has been published elsewhere. The transmission kernels used for the assessment of the minimum radius of the protection and surveillance zones are shown. Several scenarios for which control measures had to be assessed were agreed prior to the assessment. Considering that RP has been eradicated globally, a re‐emergence that is not stopped in its early phases could have a devastating impact on animal health and the economy. The panel concludes that no suitable strategies are available to entirely mitigate the risk associated with granting derogations from killing of animals in an affected establishment or for animal movements. Therefore, the panel recommends to not grant any derogations. The monitoring period of 21 days was assessed as effective, except for the hypothetical first re‐emergence of RP, when lack of awareness and diagnostic capability may extend the time to detection. It was concluded that the protection and the surveillance zones would contain 90% and > 99%, respectively, of the infections from an affected establishment. Enlarging the protection zone to 4 km would contain the disease spread with 95% probability.